PREVALENCE IN REPLACEMENT OF MISSING MANDIBULAR FIRST MOLAR AMONG YOUNG ADULT - Fareen, H.Firdus; V, Ashok; Sri, Rengalakshmi (International Journal of Psychosocial Rehabilitation, 2019)
Patients frequently need treatment to replace a single missing tooth in posterior regions, lost due to various reasons like decay, periodontal problems, injuries, impactions etc. The aim of the study was to compare the prevalence of treatment alternatives of missing mandibular first molar in young adults in a private hospital setting. Date of age, gender, type of replacement were obtained from the records at the dental hospital. Most common type of replacement of a single missing first molar is FPD (54.6%) followed by implant (40.1%). 21-30 years of age group was found to be the most common age group with replacement of single missing mandibular first with higher incidence of males. The great majority of patients with a single missing tooth had a higher interest in FPD than implants. Patients with no replacement were also prevalent.